Incidence of Workers' Compensation Claims in Opioid-Using Truck Drivers. Issue 4 (28th April 2022) - Scholl, Lindsay S.; Thiese, Matthew S.; Handy, Rodney
Abstract : This article quantifies the relationship between commercial truck driver opioid use as reported at their commercial driver medical certification examination and time to the filing of a workers' compensation claim. These results help to assess the impact that opioid use has on rates of workers' compensation claims and highlights an area in need of improvement when it comes to practitioners' prescription of opioids in safety-sensitive occupations, such as commercial truck driving. Abstract : Objective: This study examines the relationship between opioid use prevalence and subsequent filing of workers' compensation claims. Methods: A retrospective cohort study design was utilized to examine data from drivers' initial commercial driver medical exam, employment data, and workers' compensation claims data. Results: Data from 57, 733 over 7 years were analyzed. Drivers who reported opioid use at their initial medical exam visit filed subsequent workers' compensation claims 1.81 times sooner ( P  = 0.0001; 95% CI 1.34, 2.44) than drivers who did not report opioid use at their CDME when controlling for age, gender, BMI, and diastolic blood pressure. Conclusions: These findings provide information that may aid in improving regulations to control for incidents, training programs to inform professional drivers of factors that increase accident risk and educating prescribers about increased risks of injury among opioid-using drivers.